Influence in Mechanical Properties of Stir Cast Aluminium (AA6061) Hybrid Metal matrix Composite (HMMC) with Silicon Carbide, Fly Ash and Coconut coir Ash Reinforcement. (2020) - Devanathan, R.; Ravikumar, J.; Boopathi, S.; Christopher Selvam, D.; Anicia, S.A.
Abstract: The agricultural waste and industrial waste are available in abundance globally and causes risk to health as well as the environment. Thus, their effective and eco-friendly utilization has always been a challenge for scientific applications. The need for high performance materials has caused a shift in research from monolithic to composite materials. This paper presents a study on the mechanical and tribological properties of stir cast aluminium matrix Hybrid composites (MMHC) containing reinforcements using both agricultural waste (coconut shell ash) and industrial waste (fly ash) of particle size 45-50μm at four different compositions. This study mainly focuses on automobile components which frequently fails due to poor wear resistance. Test samples were casted in four different composition by varying the volume fraction of metal matrix composite and coconut shell ash. Hardness test, tensile strength test, percentage elongation were carried out to find their mechanical properties. The results shows that significant Improvement in hardness and percentage of elongation as the weight % of coconut Ash increases in MMHC.It has been observed that tensile properties decreases, as the weight % of coconut ash increases in MMHC. The optical and scanning electron micrographs of the samples indicated uniform distribution of the reinforcement particles in the matrix without any voids.